A BRIEF REVIEW ON THERAPEUTIC EFFECTS OF ORNAMENTAL PLANT ROSE - Priya Ashokrao, *Thakare; Kiran, Deshbhratar; M.N, Suryawanshi (International Journal of Ayurveda and Pharma Research, 2018)
Rosa centifolia Linn. is also known as Cabbage rose or Hundred leaved rose or Shatapatri or Taruni. It is one of the species commonly available in India. It is a complex hybrid variety developed by Dutch nurserymen in the 16th Century believed to be derived from Gallic and Damask parents. It is very well known for its perfuming and cosmetic effects. In Ayurveda it is mentioned that every plant existing in this universe is a Medicine. Rose is the best example of this saying. This Ornamental plant is having many medicinal properties which are mentioned in classics of Ayurveda and are also being critically studied through researches. Also it is used in traditional system of medicine for the management of inflammatory conditions including arthritis, cough, asthma, bronchitis, wounds, ulcers etc. Ayurveda text reveals its medicinal properties as Hridya (Cardio tonic), Medhya (Brain tonic), Twachya (Beneficial for skin), Ruchya (Enhancing taste), Vrushya (Aphrodisiac), Kushthaghna (Anti leprosy), Grahee (Absorbent) etc. researches are suggestive of various medicinal uses as Astringent, Relaxant, Nervine. We can also use it for treating Burns, Abrasions, minor wounds etc. This article briefly reviews medicinal properties of Rose according Ayurveda and various therapeutic aspects and formulations of Rose with a thorough review on recent research work.